Reducing the Pollutants from Municipal Wastewater by Chlorella Vulgaris Microalgae - Hammad, Massara Mustafa Ha; Hameed, Khalid W.; Sabti, Hussein A. (Al-Khwarizmi Engineering Journal, 2019)
In the present work, the pollutants of the municipal wastewater are reduced using Chlorella vulgaris microalgae. The pollutants that were treated are: Total organic carbon (TOC), Chemical oxygen demand (COD), Nitrate (NO3), and Phosphate (PO4). Firstly, the treatment was achieved at atmospheric conditions (Temperature = 25oC), pH 7 with time (1 – 48 h). To study the effect of other microorganisms on the reduction of pollutants, sterilized wastewater and unsterilized wastewater were used for two types of packing (cylindrical plastic and cubic polystyrene) as well as algae's broth (without packing), where the microalgae are grown on the packing then transported to the wastewater for treatment. The results showed that the other microorganism in unsterilized wastewater can slightly contribute in the treatment. Packing of cylindrical plastic is more effective than the cubic polystyrene, and microalgae's broth gives better results than the two types of packing. The treatment in the first hours was performed quickly while in the last hours, it was very slow. Then, the following parameters in the range of (temperature: 20 – 35o) pH (5 – 8), volume ratio of wastewater to microalgae's broth (1 – 2.5) were studied for sterilized wastewater and constant treatment time equal to 48 h. The results showed that the maximum reduction of pollutants are: TOC = 92.3%, NO3 = 65.2%, PO4 = 93.2% at T = 35oC, pH 8, and (wastewater/algae broth) ratio = 1, and COD = 85.6% at T = 30oC, pH 7, and (wastewater/ algae broth) ratio = 1. The temperature and pH have little effect on the reduction of pollutants compared with the wastewater/algae broth ratio. The adsorption isotherm for pollutant was also studied for three types of isotherm; linear, Freundlich, and Langmuir. The results showed that the treated pollutants are the Langmiur adsorption isotherm.